Avifauna atropelada em um trecho da br-290 no município ne São Gabriel, RS, Brasil - Rebelato, Marluci Müller (2010)
Both construction and operation of highways are considered responsible for several environmental impacts, causing disturbance, loss and habitat fragmentation and death of wildlife due roadkill. The most direct negative effect appears to be death by roadkill. Mortality of wild animals can occur when the highway crosses the habitat of certain species, and during the period of greatest activity, as breeding season or migration, when it as food availability along the highways serving as attractive to wildlife. The aim of this study was to estimate the loss of birds by roadkill on a stretch of highway BR-290, in São Gabriel, Rio Grande do Sul. The aim of this study was to estimate the loss of birds by roadkill on a highway in a region of the Pampa (BR-290) in the municipality of São Gabriel, State of Rio Grande do Sul, Brazil. The regular sampling occurred from June 2009 to May 2010. Altogether 707 specimens of birds were found killed on the highway, divided into 15 orders, 32 families and 74 species. The rate of roadkills was 137,75 individuals/km/ year. The species with the highest number of registrations were Zenaida auriculata, Sicalis flaveola, Furnarius rufus, Passer domesticus, Columbina picui, Paroaria coronata, Chrysomus ruficapillus and Nothura maculosa, respectively. Seven species of waterbirds were recorded so, the roadkill occurs when individuals move among different parts of the habitat that is fragmented by roads. Among the months of October and March were recorded six species of migratory birds. An important record was Asthenes pyrrholeuca, which is regarded as dubious record of occurrence in Brazil, consisting only in the Secondary List of the Birds of Brazil. There was a greater increase in the mortality rate in the period of high temperatures, which may be related to increased activity of species and also to the reproductive and recruitment of young.